Incidencia de los métodos y técnicas de enseñanza aprendizaje de la asignatura de matemática, en los estudiantes del décimo año de educación general básica de la unidad educativa experimental anexa a la Universidad Nacional de Loja de la parroquia San Sebastián, provincia y ciudad de Loja, periodo 2012 - 2013. Lineamientos alternativos - Chapa Faican, Wilman Fabian (2015)
From the pedagogical point, the use of methods and techniques of teaching - learning of mathematics require that teachers are trained and handled Positive Attitude to Students of SUS. In this context the objective of this research is general: To determine the incidence of Methods and Techniques in Learning of the subject of Mathematics, in grade ten students in basic general education at UNL, para This was Necessary utilization methods such as: Scientific, analytical, synthetic, descriptive, deductive, also the Technical USE As: signing, descriptive statistics, the instrument applied was the survey that, if I work with a population of 110 students and 2 teachers. The main results are: That teachers use traditional methods and techniques , due to poor planning and limited use of these strategies , preventing students to reinforce learning by solving reasoning problems , so it is important that teachers using updated methods and techniques to improve the teaching and learning of mathematics. Evaluation is a very suitable and transcendental technique for measuring the degree of knowledge of students, which allows assess the development and achievement of the objectives of the teaching and learning of mathematics.